Clinical Spectrum of HLA-B27-associated Ocular Inflammation. (4th July 2017) - Pathanapitoon, Kessara; Dodds, Emilio M.; Cunningham, Emmett T.; Rothova, Aniki
ABSTRACT: Human leukocyte antigen (HLA)-B27-associated anterior uveitis (AU) is the most commonly diagnosed form of AU and represents the largest entity of non-infectious uveitis around the world. The most typical ocular manifestation associated with HLA-B27 consists of unilateral AU of acute onset. The HLA-B27-associated acute AU represents a distinct clinical entity occurring typically in young adults between the ages of 20 and 40 years. HLA-B27-associated acute AU is typically unilateral and lasts usually several weeks and diminishes within 3 months in the majority of patients. The anterior chamber shows typically severe cellular reaction and flare, as well as a fibrinous exudate. Frequently, posterior synechiae are formed and occasionally hypopyon is present. The pattern of the disease is recurrent with a full remission between the attacks. Intraocular pressure during active periods is typically low due to inflammation of ciliary body and decreased aqueous production. Less typical presentations are also recognized and include the development of chronic inflammation, posterior segment involvement, episcleritis, and scleritis. An isolated retinal vasculitis in HLA-B27-positive patients may develop, mostly in those with inflammatory bowel disease. Chronic AU, which may be either unilateral or bilateral affects up to 20% of patients. Ocular complications of HLA-B27-associated AU are diverse and include commonly posterior synechiae, cataract, glaucoma and/or hypotony. The visual outcome and complications of HLA-B27-associated AAU are frequently being compared with HLA B27-negative patients with AU and show that the prognosis of HLA-B27-associated uveitis is rather favorable, as <2% developed legal blindness and <5% visual impairment. A novel algorithm called the "Dublin Uveitis Evaluation Tool (DUET)" has been proposed to guide ophthalmologists to refer appropriate HLA-B27-positive patients with uveitis to rheumatologists.